THE ROLE OF TECHNOLOGY IN ENHANCING STUDENT ENGAGEMENT AND LEARNING OUTCOMES - E’zoza Xolboyeva,; Sabrina Jumanova, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article investigates the role of educational technology in improving student engagement and learning outcomes in English language instruction. Through a blend of theoretical perspectives and classroom-based research, it explores how digital tools—ranging from AI-powered assistants to collaborative platforms—transform learning environments by promoting motivation, autonomy, and academic success. The study employs Constructivist, Connectivist, and Cognitive Load theories to evaluate how students interact with digital technologies and how these tools can be integrated to enhance the teaching-learning process. The findings provide evidence that when implemented thoughtfully, educational technologies significantly improve both engagement and performance in language classrooms.